A rare complication seen in a child diagnosed with acute lymphoblastic leukemia: Isolated penile gangrene - Richa Chauhan; Gyanendra Singh; U.P Singh (International Journal of Medical Research and Review, 2016)
Leukemia is the most common cancer seen in children with acute lymphoblastic leukemia, accounting for 80% of all childhood leukemias and 24% of all cancers in children. The intensive chemotherapy regimen used in the treatment is often associated with a number of complications. Thromboembolic events in the form of coagulopathy and thrombosis have been reported in patients of acute leukemia undergoing chemotherapy. In the present study, we report the case of a 10-year-old boy with acute lymphoblastic leukemia (ALL) who developed dry gangrene of the penis while on chemotherapy. Dry gangrene of the penis is a rare complication, in view of the presence of extensive collateral circulation in the region. This presentation may be correlated to a rare thrombotic complication, associated with hypercoagulable status seen in leukemic patients undergoing chemotherapy.